Prevalence of Mitral Annular Calcification in Nepalese Chronic Kidney Disease Patients Under Hemodialysis in A Tertiary Care Centre of Western Nepal - Adhikari, Suman; KC, Amrit; Shrestha, Jujuraj; Thakuri, Surya Bahadur Hamal; Poudel, Rajendra; Kumal, Kamal; Ghimire, Sunita; Tamrakar, Dhiraj; Devkota, Sandesh; Sahi, Ravi; Manandhar, Varsha (Nepalese Heart Journal, 2025)
Background and aims: Mitral annular calcification (MAC) is a chronic process. Elderly patients have a higher prevalence of MAC. Chronic kidney disease(CKD) patients and cases with multiple cardiovascular risk factors have a higher chance of having MAC. MAC is associated with higher chances of having major adverse cardiovascular events (MACE). MAC is more common in CKD patients, probably because of abnormal calcium and phosphorus metabolism. The main aim of our study is to find out the prevalence of mitral annular calcification in chronic kidney disease patients under hemodialysis. Methods: It was a prospective, observational, and single-centered study conducted in the department of internal medicine, Pokhara Academy of Health Sciences(POAHS), Nepal. This study was conducted over a period of a year between 9th November 2022 and 8th November 2023. Patients with CKD under maintenance hemodialysis(MHD) were enrolled. Data (Age, Sex, HD duration and frequency, presence of other risk factors like Hypertension, DM, smoking, history of coronary angiography and revascularization, electrocardiography for MAC, left ventricular systolic and diastolic functions (LVEF and LVDD), left ventricular hypertrophy ) were collected after complete history taking followed physical examination, relevant laboratory investigations, and transthoracic echocardiography(TTE). Statistical analysis (descriptive analysis for proportion and percentage, and 2x2 contingency table for odds ratio and bivariate analysis) was performed using the latest version of SPSS. Results: The total number of patients enrolled was 121. The mean age of the cases enrolled was 54.26 years (SD=15.25). The majority were male patients (67%). 111(91.74%) were hypertensives, and 40 (33%) were diabetics. MAC was found in 36 (29.75%) of patients enrolled. 6.6% patients had coronary artery disease(CAD) and 1.65% underwent coronary revascularization in past. Higher odds of having MAC were observed in CKD patients with smoking (OR=10.13), HD duration>12 months (OR=4.24), DM(OR=2.86), and HTN(OR=1.77). However, in binary regression analysis after adjusting for confounders, the AORs for age, HD duration, and DM were 9.8, 13.3, and 3.3, respectively. Conclusion: There is a high prevalence of MAC in CKD patients under maintenance HD. Advanced age, CAD, longer duration of HD, DM, HTN, and smoking are important factors associated with MAC.TTE is an important tool to detect MAC in CKD patients.